PERAN SUKU DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KOTA ADMINISTRASI JAKARTA TIMUR DALAM MENINGKATKAN KUALITAS PERMUKIMAN DI JAKARTA TIMUR TAHUN 2023 - Fergrinov, Chris; Zebua, Ben Hansel Notatema (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The high level of urbanization in East Jakarta has led to an increase in slum areas that do not meet health, safety, and housing standards. Specifically, East Jakarta has recorded that 12% of its settlements are classified as slums, with 78 neighborhood associations (RW) identified as problematic. Through the implementation of the Community Action Plan (CAP) and Collaborative Implementation Program (CIP), the government is striving to make participatory improvements, including physical restructuring, socio-economic strengthening, and basic infrastructure development. This study aims to analyze the extent of the role of the Sub-Department in the implementation of these programs in improving the quality of settlements in East Jakarta in 2023. This study uses a qualitative descriptive method through interviews using purposive sampling techniques. This study found that the Sub-Department plays three important roles: as a regulator through the formulation of verification rules and program priority setting; as a facilitator through the provision of basic infrastructure such as drainage, road access, and open spaces; and as a dynamizer through education, socialization, and increased community participation. These roles contribute to improving the residential environment, despite limitations in resources and coordination. Strengthened collaboration among various actors is needed to support sustainable residential development. Keywords : Role, Quality of Housing, Housing Areas